ANALYSIS OF THE RELATIONSHIP BETWEEN SUPPLY CHAIN MANAGEMENT AND BUSINESS PERFORMANCE IN THE CREATIVE ECONOMY SECTOR - Agustini, I Gusti Ayu Ari; Sudjiman, Lorina Siregar; Bagenda, Christina (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
In the rapidly developing digital era, this sector faces significant challenges and opportunities influenced by the company's ability to manage supply chains, implement innovation, and utilize technology effectively. This research analyzes the relationship between supply chain management (SCM), innovation, technology orientation, and business performance in the creative economy sector. The research method involves a quantitative approach, which involves collecting data through surveys distributed to companies in the creative economy sector. The questionnaire is designed to regularly measure the dimensions of SCM, innovation, technology orientation, and business performance. Following the results of data analysis, it is confirmed that supply chain management, innovation, and technology orientation have a positive and significant effect on business performance. This research provides significant implications for companies in the creative economy sector by showing how efficient supply chain management, implementation of sustainable innovation, and robust technology orientation can improve overall business performance. By understanding the relationship between these factors, companies can develop more effective strategies to improve operational efficiency, accelerate new product development, and leverage technology to gain competitive advantage.